2009
DOI: 10.1097/mbc.0b013e32831be9ad
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxinemia-induced changes in coagulation as measured by rotation thrombelastometry technique and conventional laboratory tests: results of a pilot study on pigs

Abstract: Modified rotation thrombelastometry (ROTEM) is widely used in near-patient assessment of hemostasis, but data on functional consequences initiated by acute endotoxinemia are rare. To test the hypothesis that the ROTEM technique allows detection of endotoxinemia-induced changes in hemostasis, we conducted a pilot study on pigs. Fifteen healthy pigs were anesthetized and instrumented for invasive hemodynamic monitoring. Several coagulation tests and the ROTEM assay were performed at baseline and 60 min after adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
2
9
1
Order By: Relevance
“…This has been documented by TEG/ROTEM and has been reproduced in studies using experimental human [23] and animal [25][27] models of endotoxemia [23], [25][27]. Also, platelet aggregation is profoundly reduced in septic patients [19][22] and decreases with disease severity [20]–[22], which has also been reproduced in experimental human [23], [24] and animal [28], [29] models of endotoxemia.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This has been documented by TEG/ROTEM and has been reproduced in studies using experimental human [23] and animal [25][27] models of endotoxemia [23], [25][27]. Also, platelet aggregation is profoundly reduced in septic patients [19][22] and decreases with disease severity [20]–[22], which has also been reproduced in experimental human [23], [24] and animal [28], [29] models of endotoxemia.…”
Section: Discussionmentioning
confidence: 86%
“…Multiple Platelet function Analyzer; Multiplate®, Verum Diagnostica GmbH, Munich, Germany) [8] reveal both fibrinolysis and platelet function. Several studies have characterized the coagulopathy in sepsis [9][22] and experimental human [23], [24] and animal [25][29] endotoxemia by these tests.…”
Section: Introductionmentioning
confidence: 99%
“…In sepsis, increased endothelial synthesis of plasminogen activator inhibitor-1 (PAI-1) has been shown to be the main inhibitor of fibrinolysis [4,5]. The balance between clot formation and fibrinolysis has been difficult to investigate; the readily available conventional coagulation tests may be misleading [8,9], and fibrinolysis has been difficult to accurately quantify despite measuring the fibrin degradation product-D-dimer.…”
Section: Introductionmentioning
confidence: 98%
“…The principle advantage of thromboelastometry is its ability to quickly reflect the end-result of complex interactions between all components of the hemostatic system (including cells). Thromboelastometry has already been shown to be a highly sensitive assay capable of detecting distinct, and very early as well as late changes in coagulation in endotoxemia and severe sepsis [8,9]. It also provides information about fibrinolysis using parameters such as "maximum lysis" (ML) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we demonstrated that endotoxinemia can be detected with thromboelastometry under in vitro conditions [5]. Thromboelastometric variables remained within reference ranges during the course of critically illness in 30 patients with sepsis [6]. In another study, however, early changes in thromboelastometry values were demonstrated in endotoxin-treated pigs [7].…”
Section: Introductionmentioning
confidence: 99%